2017
DOI: 10.1108/ijlma-10-2016-0088
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects orientation and innovation strategy on the effect of uncertainty on the performance of business environment

Abstract: Purpose This research aims to examine the moderating effect of strategic orientation on the effect of environmental uncertainties on business performance and the moderating effect of innovations on the effect of environmental uncertainties on performance of the business in the aviation industry in Indonesia. Design/methodology/approach Research data were collected in stages by means of interviews with corporate leaders of Indonesian airlines and branch managers of several airports, as well as with the Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
1
29
2
1
Order By: Relevance
“…This study agrees with the results of Yaghoobi et al (2014), which revealed that organizational agility is a source of competitive advantage when it forces competitors to compete and imitate. Organizational agility is the primary source for small businesses to achieve a competitive advantage (Fernandes and Solimun 2017;Wang and Ahmed 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This study agrees with the results of Yaghoobi et al (2014), which revealed that organizational agility is a source of competitive advantage when it forces competitors to compete and imitate. Organizational agility is the primary source for small businesses to achieve a competitive advantage (Fernandes and Solimun 2017;Wang and Ahmed 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are four assumptions that must be fulfilled, namely, linearity assumption, non-multicollinearity assumption, normality assumption and non-heteroscedasticity assumption. The linearity assumption uses Ramsey Reset Test approach (Fernandes, 2017). The assumption is fulfilled if the value of Sig F is > 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…Non-heteroscedasticity assumption uses Breuch Pagan Test approach. The assumption met if the value of Sig BP is > 0.05 (Fernandes, 2017). The assumption test results in Table IV show that all assumptions met.…”
Section: Resultsmentioning
confidence: 99%
“…The data analysis used to solve hypothetical model built in this research is partial least square (PLS). Using WarpPLS package computer program (Fernandes and Solimun, 2017), the research uses the following hypotheses:…”
Section: Methodsmentioning
confidence: 99%